PENEGAKAN HUKUM PASAL 70 UNDANG-UNDANG NOMOR 10 TAHUN 2016 TENTANG PEMILIHAN GUBERNUR, BUPATI, DAN WALIKOTA DALAM PELAKSANAAN PEMILIHAN KEPALA DAERAH DAN WAKIL KEPALA DAERAH SERENTAK DI KOTA PEKANBARU TAHUN 2017 - Nurazmi Darma Oktasia; Mexsasai Indra; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The regions that will hold the election consist of 7 Provinces, 76 Regencies, and 18 Cities. One of them is Pekanbaru City. 5 pairs of Mayor of Pekanbaru 2017, in the implementation of campaign by all Mayor and Vice Mayor Candidates there is a violation involving parties that are prohibited by legislation to assist in campaign process.The purpose of writing this thesis are: First, law enforcement in Article 70 of Law Number 10 Year 2016 on the Election of Governors, Regents and Mayors in the election of Regional Heads and Deputy Heads of Regions simultaneously in Pekanbaru City, Second, law enforcement inhibiting factors in Article 70 of Law Number 10 Year 2016 on the Election of Governors, Regents and Mayors in the election of Regional Heads and Deputy Regional Heads simultaneously in Pekanbaru City, Third, the efforts made to overcome the obstacles of law enforcement in Article 70 of Law Number 10 Year 2016 About the election of Governors, Regents and Mayors in the implementation of the election of Regional Head and Deputy Regional Heads simultaneously in Pekanbaru City. The type of research conducted in this study the author uses the type of sociological law research, research location in this study is Pekanbaru City. Population and sample are all parties related to the problem under study. Sources of data used are: primary data, secondary data, data collection techniques using unstructured interviews.From the research results there are three main issues that can be concluded. Firstly, the enforcement of the law of Article 70 is not in accordance with the rules contained in the Law on Regional Head Election, Second, the Factor inhibiting law enforcement in Article 70 of Law Number 10 Year 2016 on the Election of Governors, Regents and Mayors in the Implementation of the Election of Regional Head and Deputy Head of Serentak Region in Pekanbaru City is: there is fear of loss of position, political interest factor, political promise given to ASN, Internal Panwaslu factor, Third, Efforts made to overcome obstacles Law Enforcement Article 70 Law Number 10 Year 2016 about the election Governor, Regent, and Mayor in the implementation of elections of Regional Head and Deputy Regional Heads simultaneously in Pekanbaru City are: Providing socialization to ASN / PNS, emphasizing to ASN / Civil Servants regarding their alignment only to the people's interest, monitoring ASN / Civil Servants so as not to eat political promises . Author suggestion, Firstly, It is expected that supervision done by law enforcers in the future is better, there should be no system of tolerance to the enforcement of election rules. Law enforcers are expected to perform their duties in accordance with the prevailing regulations, The existence of transparency of law enforcement in following up reports or findings are reported. It is expected that the revision of the legislation related to the sanctions either be criminal sanctions or administrative sanctions for candidate pair and ASN / Civil Servants and it is expected that the addition of provisions concerning membership of District / Municipal Panwaslu (human resources) amounting to only 3 people related to the provisions of Article 72 paragraph 2) point c of Law Number 15 Year 2011 regarding the Implementation of General Elections.Keywords: Law Enforcement - Election Implementation – Regional Head